Pengembangan Media Pembelajaran Powerpoint Interaktif untuk Keterampilan Membuat Pantun pada Siswa Kelas V Sekolah Dasar - Listy Sri Mulyani; Dadan Djuanda; Cucun Sunaengsih (Jurnal Pena Ilmiah, 2022)
This research was motivated by the findings which showed that students' activities were passive in participating in learning because the learning method used by the teacher was not appropriate and the use of learning media was less interactive. material and cannot rhyme itself. The research model used is DD. Data collection techniques used are interviews, observations and validation sheets of media experts and material experts. The results showed that the interactive PowerPoint learning media developed by the researchers got a final score of 90% from content experts. Meanwhile, media experts got a final score of 86%. This means that interactive powerpoint learning media is very feasible to use based on the conversion of assessment criteria. This interactive PowerPoint packaging material is presented in a simple and attractive form so that it will improve students' skills in making rhymes.